ANALISIS PENGARUH KEBIJAKAN EKONOMI MAKRO TERHADAP KINERJA KEUANGAN PERUSAHAAN DI INDONESIA: Inflation, Interest Rate; Exchange Rate; Gross Domestic Product (GDP); Financial Performance; Macroeconomic Policy - Dewa Brata; Sarmini; Imam Setiawan; Bambang Satriawan; Ely Kurniawati (Zona Manajemen: Program Studi Magister Sains Manajemen Universitas, 2026)
This study aims to analyze the effect of macroeconomic policy on the financial performance of companies in Indonesia. The macroeconomic variables examined include inflation, interest rates, exchange rates, and gross domestic product (GDP), while financial performance is measured using Return on Assets (ROA) and Return on Equity (ROE). This research employs a quantitative approach utilizing secondary data from 2014–2024 obtained from the Central Bureau of Statistics (BPS) and the Indonesia Stock Exchange (IDX). The findings reveal that interest rates and inflation have a significant negative effect on both ROA and ROE, while GDP and exchange rates show a positive relationship. The results provide useful insights for policymakers, investors, and business actors to adapt financial strategies to macroeconomic policy changes.